2019
DOI: 10.1103/physrevlett.122.192001
|View full text |Cite
|
Sign up to set email alerts
|

Muon-Electron Scattering at Next-To-Next-To-Leading Order: The Hadronic Corrections

Abstract: The Standard Model prediction for muon-electron scattering beyond leading order requires the inclusion of QCD contributions which cannot be computed perturbatively. At next-to-and next-tonext-to-leading order, they arise from one-and two-loop diagrams with hadronic vacuum polarization insertions in the photon propagator. We present their evaluation using the dispersive approach with hadronic e + e − annihilation data and estimate their uncertainty. We find that these corrections are crucial for the analysis of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(61 citation statements)
references
References 63 publications
0
61
0
Order By: Relevance
“…been computed recently in refs. [30,31]. Further theoretical progress in the calculation of NNLO corrections and resummation was presented at the MITP topical workshop "The evaluation of the leading hadronic contribution to the muon anomalous magnetic moment ", held in Mainz in February 2018.…”
Section: Jhep02(2019)155mentioning
confidence: 99%
“…been computed recently in refs. [30,31]. Further theoretical progress in the calculation of NNLO corrections and resummation was presented at the MITP topical workshop "The evaluation of the leading hadronic contribution to the muon anomalous magnetic moment ", held in Mainz in February 2018.…”
Section: Jhep02(2019)155mentioning
confidence: 99%
“…Finally, in section 5 we showed that the numerical evaluation of these irreducible diagrams gives results in agreement with the standard dispersive approach and -when the analytic expression of Π lep (q 2 ) is employed -in agreement with analytic two-loop vertex results in QED. A complete calculation of the hadronic corrections to µ-e scattering at NNLO with the dispersive approach will be presented soon [36]. valuable suggestions.…”
Section: Discussionmentioning
confidence: 99%
“…To reach the target precision these corrections have to be known at a level of 10 ppm as well. The effect of hadronic corrections was recently addressed in [56,57] using two independent methods. At leading order also Z-exchange has to be taken into account.…”
Section: Muon-electron Scattering With M Mmentioning
confidence: 99%
“…Also at NNLO the correction due to hadronic and leptonic VP is included. These contributions are split up according to the classification of [57]. The diagrams where the VP factorises are implemented in em2emAA, em2emAR, and em2emAF.…”
Section: Running M M For Muon-electron Scatteringmentioning
confidence: 99%